Assessment of the Effects of Sanctions on trade between the EU and Russia - Hašková, Barbara; Klosová, Anna, 1942-; Coniglio, Nicola; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2015)
This thesis concerns about the effectiveness of sanctions imposed between Russia and the EU in 2014. Firstly are conducted theoretical foundations of sanctions and their imposition from the EU as well as Russian contra-sanctions. Secondly, the analysis is based on the gravity model in trade in log-linear form and further develop out-of-sample estimations about trade potentials. Although trade potentials did not proved the expected decrease in exports from EU to Russia, the Input-Output analysis of impacts on exports of food products did so. Results yielded calculated impacts on GDP of various countries due to food embargo that are more or less comparable with the actual evolution of GDP and trade flows. Thirdly, the indirect effects of sanctions of third country effect and re-exports are observed from trade patterns. There has been recorded increased exports of food related products from the EU towards members of Euroasian Customs Union as well as increased imports from these countries to Russia. Finally, the results points out decreased economic activity of Russia due to depreciation of domestic currency, capital flight, decline in oil prices and also sanctions adding up to the problems the economy deals with. The economic impacts of sanctions are present in both parties. However, from the political view sanctions did not proved to be effective so far. Russian intervention in Ukraine territory is continuing.
Vedoucí práce: Anna Klosová
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2016
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2016
Způsob přístupu: Internet
Keywords: economics of globalisation and european integration [obor dipl. práce]; diplomové práce; master's theses